PENGAWASAN CEMARAN RESIDU PESTISIDA PADA PANGAN SEGAR ASAL TUMBUHAN (PSAT) DI KABUPATEN MINAHASA - Pertiwi, Saptya Fajar (Journal of Integrated Agricultural Socio-Economics and Entrepreneurial Research (JIASEE), 2023)
Fresh food from plant origin (PSAT) has characteristics which are susceptible to insect pests and plant diseases. Consequently, utilization of pesticides can be used as an alternative for farmers, as the result, PSAT is often polluted by pesticide residues. Factor of food quality and safety are the main problems in product improvement and marketing of PSAT, it must be a concern of farmers, traders and consumers for quality and health. Improper post-harvest handling, the use of fertilizers and pesticides that are not in accordance with regulations have brought Indonesian PSAT products to a low food safety guarantee status and a high level of contamination.The aims of this study is to determine the level of contamination of pesticide residues on cayenne pepper, curly chilies, tomatoes, cabbage, and celery. There were 30 types of pesticides tested, including: gamma chlordane; 2.4-DDT; 4.4-DDD; 4.4-DDE; 4.4-DDT; aldrin; alpha-BHC; beta-BHC; chlordane; chlorothalonyl; cis-chlordane; DDT; dichlorant; dieldrine; endosulfan; endosulfan I; endosulfan II; endosulfan sulfate; endrine; gamma-BHC; heptachlor; heptachlor epoxide; hexachlorbenzene; oxychlordane; quintozene; technazene; transchlordant; dicofol; methoxychlor; tolclofos-methyl in PSAT samples which obtained from groups of female farmers and traders in East Langowan, West Langowan and North Tondano. The results showed that all of the samples contributed the number of pesticide residues below the maximum pesticide residue limit (BMR), thereby PSAT relatively safe for consumption. In fact, women farmer groups and traders in East Langowan, West Langowan and North Tondano are aware on the dangers effect by using pesticides at every stage of agriculture which can cause pesticide residues may be remained in agricultural product which provide negative impact on human health and environment